2015
DOI: 10.1111/his.12593
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal monophasic synovial sarcoma is a morphological and immunohistochemical mimic of gastrointestinal stromal tumour

Abstract: A diagnosis of synovial sarcoma should be considered particularly if an abdominal spindle cell neoplasm shows a haemangiopericytomatous pattern and diffuse CD99 and CD56 immunopositivity. A confident distinction between abdominal synovial sarcoma and GIST requires KIT/PDGFRA mutation analyses and specific molecular testing for synovial sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In testicular tissues, DOG1 immunoreactivity is observed in spermatocytes, spermatids and the luminal borders of the epididymis and rete testis . The various tumor types reported to express DOG1 are presented in Table . In particular, DOG1 immunoexpression in salivary gland tumors has been investigated in detail, and DOG1 has been practically applied as a marker of salivary acinar and intercalated duct differentiation .…”
Section: Dog1 Immunohistochemical Expression In Various Tumor Types Omentioning
confidence: 99%
“…In testicular tissues, DOG1 immunoreactivity is observed in spermatocytes, spermatids and the luminal borders of the epididymis and rete testis . The various tumor types reported to express DOG1 are presented in Table . In particular, DOG1 immunoexpression in salivary gland tumors has been investigated in detail, and DOG1 has been practically applied as a marker of salivary acinar and intercalated duct differentiation .…”
Section: Dog1 Immunohistochemical Expression In Various Tumor Types Omentioning
confidence: 99%
“…11 A clinical summary of the 36 cases of primary gastric synovial sarcoma, including our case, is shown in the Table. [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23] When a gastric spindle cell tumour is encountered, the differential diagnosis mainly focuses on other gastrointestinal mesenchymal tumours, such as GIST, leiomyoma, leiomyosarcoma, schwannoma and fibromatosis. Appropriate immunohistochemical staining is crucial in order to make a diagnosis of synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Early in tumorigenesis, an angiogenic switch is activated by hypoxia, promoting the expression of pro-angiogenic growth factors, such as the VEGF family, its receptors, and HIF1α among others [7]. Recent publications have highlighted the difficulties in differentiating between GIST and monophasic intra-abdominal SS, where molecular mutations are sometimes the only distinguishing feature [27]. It has been suggested that it would be particularly informative to explore possible relationships between the presence of vasculogenic structures and the response to antiangiogenesis therapy [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis with a high-grade GIST may be difficult [26, 27]. Both tumour types cause metastasis and display an aggressive behaviour, suggesting that molecular reorganisations such as of SYT–SSX gene translocation and KIT mutations might be similarly essential for the growth of angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation